Ideas fatalistas ante el posible contagio de la COVID-19 según el tipo de enfermedad que padecían los pacientes peruanos. - Rodriguez-Alarcon, J.F. (2021)
It has been observed that some groups of patients had the perception that if they fell ill from COVID-19 they could have greater complications. The aim of this study was to determine the association between fatalistic thinking about the possible infection of coronavirus according to the type of disease suffered by Peruvian patients. An analytical study of secondary data was carried out, which used a previous data to obtain respondents who had a disease (according to 9 groups/medical specialties), and cross-checked this according to fatalistic thinking (from a validated test). Of the 4483 respondents, 15% had a disease. Those with a respiratory disease perceived that they would be complicated post infection (p<0.001), also those with a cancer or tumor (p<0.001) or those with an endocrinological disease (p=0.002). Those who thought they would become depressed if they became ill were those with a respiratory (p=0.013) or gastroenterological disease (p=0.001). Those who perceived that they might die were those with a respiratory disease (p<0.001), those with any cancer or tumor (p=0.007), endocrinological (p<0.001) and neurological or psychiatric diseases (p<0.001). They could make a fatal decision upon learning of the infection are those who had an endocrinological disease (p=0.039). In conclusion, some groups of patients have a higher perception of getting sick, getting complicated, dying or even taking other fatal actions after learning that they have coronavirus infection; therefore, they should be given psychological support.